2022
DOI: 10.3390/ijerph19148291
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Inclusive Leadership and Pro-Social Rule Breaking in Hospitality Industry: Important Role of Psychological Safety and Leadership Identification

Abstract: This study aims to empirically examine the mediating effects of psychological safety and leadership identification on the relationship between inclusive leadership and pro-social rule breaking among hospitality employees. This study analyzes the survey data collected in three waves from 589 employees working in different hotels and restaurants operating in the Northern areas of Khyber Pakhtunkhwa, Pakistan. The scale validity, composite reliability, and hypotheses were assessed through PLS-SEM. The study found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…For this study, SmartPLS 4 was employed to analyze the data. Most recent management research projects have used the PLS-SEM method for data analysis [ 75 , 76 , 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…For this study, SmartPLS 4 was employed to analyze the data. Most recent management research projects have used the PLS-SEM method for data analysis [ 75 , 76 , 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, this study uses IL as a moderating variable and found that when employees’ IL, the relationship of ML–SS is strengthened, which would make the model more accurate. Theoretically, the current study mainly uses IL as a mediating variable ( Khattak et al, 2022 ). but our research select IL as a moderating variable, further enriching the findings in this area and highlighting the need and urgency for further research on IL.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of outcome variables, identification with a leader impacts employees’ work attitude, behavior, and performance ( Lührmann and Eberl, 2016 ). Some scholars have considered it a mediating variable between inclusive leadership and employee voice or prosocial behavior ( Khattak et al, 2022 ), or between moral leadership and inhibitory feedback. Furthermore, existing studies take identification with a leader as a moderating variable between charismatic leadership and innovation performance of employees ( Zhao et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nonetheless, there is still much to learn about the fundamental processes through which socially responsible leadership affects worker engagement in the education sector . Insufficient research specifically addressing these ideas in university setting has resulted in the majority of prior research on socially responsible leadership, job engagement, and psychological safety focusing on different industries (Ahmad et al, 2022;Khattak et al, 2022;. Furthermore, there is a dearth of research that combines the effects of job engagement, leadership style that is socially responsible and psychological safety in a single study, especially in the field of education, despite earlier studies looking at these aspects independently.…”
Section: Introductionmentioning
confidence: 99%